The outcomes of recent patient safety education interventions for trainee physicians and medical students: a systematic review. Issue 5 (20th May 2015) - Kirkman, Matthew A; Sevdalis, Nick; Arora, Sonal; Baker, Paul; Vincent, Charles; Ahmed, Maria
Abstract : Objective: To systematically review the latest evidence for patient safety education for physicians in training and medical students, updating, extending and improving on a previous systematic review on this topic. Design: A systematic review. Data sources: Embase, Ovid Medline and PsycINFO databases. Study selection: Studies including an evaluation of patient safety training interventions delivered to trainees/residents and medical students published between January 2009 and May 2014. Data extraction: The review was performed using a structured data capture tool. Thematic analysis also identified factors influencing successful implementation of interventions. Results: We identified 26 studies reporting patient safety interventions: 11 involving students and 15 involving trainees/residents. Common educational content included a general overview of patient safety, root cause/systems-based analysis, communication and teamwork skills, and quality improvement principles and methodologies. The majority of courses were well received by learners, and improved patient safety knowledge, skills and attitudes. Moreover, some interventions were shown to result in positive behaviours, notably subsequent engagement in quality improvement projects. No studies demonstrated patient benefit. Availability of expert faculty, competing curricular/service demands and institutional culture were important factors affecting implementation. Conclusions: There is an increasing trend for developing educational interventions in patient safety delivered to trainees/residents and medical students. However, significant methodological shortcomings remain and additional evidence of impact on patient outcomes is needed. While there is some evidence of enhanced efforts to promote sustainability of such interventions, further work is needed to encourage their wider adoption and spread.